1980
DOI: 10.1016/s0022-5347(17)55687-6
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Exploration of the Unilateral Acute Scrotum in Young Male Subjects

Abstract: Physical exertion, sexual activity or trauma can precipitate cremasteric contraction and result in torsion of a testicle with an underlying congenital anomaly. A high index of suspicion is required by the primary care doctor if acute torsion is to be diagnosed early for immediate reduction. The duration of torsion and the degree of twisting determine the long-term salvage rate of testicular tissue. An aggressive policy of immediate exploration of the unilateral acute scrotum in young men resulted in exploratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(41 citation statements)
references
References 16 publications
2
33
0
2
Order By: Relevance
“…Twenty–nine patients (55.8%) demonstrated an elevation of body temperature of 38°C or more. This was comparable to results reported by Cass et al [19]who found 54.7% of patients with an epididymitis having a WBC of 10/nl or more and 34.6% with a body temperature above 100°F.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Twenty–nine patients (55.8%) demonstrated an elevation of body temperature of 38°C or more. This was comparable to results reported by Cass et al [19]who found 54.7% of patients with an epididymitis having a WBC of 10/nl or more and 34.6% with a body temperature above 100°F.…”
Section: Discussionsupporting
confidence: 91%
“…Before the introduction of ultrasound to clinical practice the rate of unnecessary operative explorations of patients with an acute scrotum was higher than today. In a study by Cass et al [19]115 patients of 172 (66.9%) with an epididymitis were reported. Furthermore, there were 40 patients with suspected testicular torsion.…”
Section: Discussionmentioning
confidence: 99%
“…Direct trauma was found in only 15% of the 20 TT cases, but in most cases no precipitating factors were elicited. Trauma has been mentioned as a precipitating cause of TT in as many as 48% of cases in some series [11]. While cold weather was implicated in at least one review [12], an increase in the incidence of torsions in winter was not found in the Al-Jahra series.…”
Section: Resultsmentioning
confidence: 97%
“…[10][11][12][13][14] In 1967, Leape 15 cautioned the diagnostic error in testicular torsion is due to the "failure of the majority of cases to conform to the accepted clinical picture." Atypical presentations of testicular torsion likely present a diagnostic enigma in that history of illness, physical examination, and imaging may distract from the true diagnosis.…”
Section: Discussionmentioning
confidence: 99%